Characterization of 1, 4‐Dihydropyridine Derivatives by Electrospray Ionization Ion‐Trap Time‐of‐Flight Tandem Mass Spectrometry. (8th September 2015) - Wei, Qiang; Yan, Guoquan; Li, Qianrong
<x xml:space="preserve">Abstract</x> 1, 4‐Dihydropyridines provide the principal structural components for calcium channel blockers, which are usually studied by expeditious qualitative and quantitative analyses in pharmaceutical research and development. In this work, through the use of high‐resolution electrospray ionization ion‐trap time‐of‐flight multistage tandem mass spectrometry (ESI‐IT‐TOF/MSn ), the accurate masses and fragmentation pathways of protonated derivatives (1–12) of 1, 4‐dihydropyridine derivatives are determined and rationalized. All protonated molecules are further fragmented by loss of the neutral groups 4‐R1H, 3‐C2H4, 5‐C2H4, R2OH, or CO, yielding three fragmentation pathways with two different fragment nuclei of pyridine or 1, 4‐dihydropyridine. During the formation process of the pyridine nucleus, one pathway is that product ions at m/z 224 or 252 are the common diagnostic masses in most compounds; the other pathway is that the product ions are obtained by the loss of R2OH. The 1, 4‐dihydropyridine nucleus in three compounds arises from double C2H4 elimination. Simultaneously, this study supplies abundant special fragment information, which potentially provides a new method for structural studies of 1, 4‐dihydropyridine derivatives.